The valuation of patents using third-party data: the Ocean Tomo 300 Patent Index. Issue 42 (7th September 2016) - Mauck, Nathan; Pruitt, Stephen W.
ABSTRACT: This study is the first investigation of the ability of the financial marketplace to value patent assets via exploiting the informational content of a widely quoted stock market patent index known as the Ocean Tomo 300 Patent Index (OT 300). The results suggest that the OT 300 'works, ' in the sense that the index generates buy-and-hold returns economically and statistically in excess of those of the market as a whole as well as a specially created 300-firm benchmark portfolio composed of other very liquid patent-holding firms.